The influence of functionality and innovativeness of smart service systems on customer’s impulse buying behaviors - Chuang, Shu-Hui; Ou, Cheng-Chieh; Lin, Shinyi (Edelweiss Applied Science and Technology, 2024)
This research aims to analyze the effect of two external factors—the functionality and innovativeness of smart service systems (SSSs)—on customers’ impulse purchasing behavior using the stimulus-organism-response (SOR) model. We collected data using a questionnaire survey, yielding 272 valid responses. The data was then analyzed using structural equation modeling (SEM). The study found that SSS functionality and innovativeness positively influenced experience value, which in turn significantly affected perceived pleasure and usefulness, promoting impulse buying behaviors. This study examines how external environmental stimuli in SSSs prompt impulse buying using the SOR framework, focusing on "experience value." The study found that SSS functionality enhances time-saving, usefulness, customer involvement, and business scale, leading to increased service use and positive customer experiences, ultimately promoting impulse buying behaviors. This study contributes to academic knowledge by integrating experience value into the S-O-R framework, demonstrating that SSS functionality and innovativeness significantly enhance customer experience value, perceived usefulness, and pleasure, thereby promoting impulse buying behaviors. The study shows smart meal-ordering systems enhance efficiency and customer satisfaction. Operators should optimize system value, expand payment options, improve service quality, and use visual and social marketing to boost customer engagement and impulse buying behaviors.